Sulfate removal from wastewater using ettringite precipitation: Magnesium ion inhibition and process optimization. - Dou, Weixiao; Zhou, Zhen; Jiang, Lu-Man; Jiang, Aijian; Huang, Rongwei; Tian, Xiaoce; Zhang, Wei; Chen, Dongqing (Journal of Environmental Management, 2017)
One of the main challenges in industrial wastewater treatment and recovery is the removal of sulfate, which usually coexists with Ca 2+ and Mg 2+ . The effect of Mg 2+ on sulfate removal by ettringite precipitation was investigated, and the process was optimized in the absence and presence of Mg 2+ . In the absence of Mg 2+ , the optimum conditions with sulfate removal of 99.7% were obtained at calcium-to-sulfate ratio of 3.20, aluminum-to-sulfate ratio of 1.25 and pH of 11.3 using response surface methodology. In the presence of Mg 2+ , sulfate removal efficiency decreased with increasing Mg 2+ concentration, and the inhibitory effect of Mg 2+ matched the competitive inhibition Monod model with half maximum inhibition concentration of 57.4 mmol/L. X-ray diffraction and Fourier transform infrared spectroscopy analyses of precipitates revealed that ettringite was converted to hydrotalcite-type (HT) compound in the presence of Mg 2+ . The morphology of precipitates was transformed from prismatic crystals to stacked layered crystals, which confirmed that Mg 2+ competes with Ca 2+ for Al 3+ to form HT compound. A two-stage process was designed with Mg 2+ removal before ettringite precipitation to eliminate the inhibitory effect, and is potential to realize sludge recovery at the same time of effective removal of sulfate and hardness.